A ‘Healthy’ Hot Cuppa - Kumar, P. Praveen; Prasad, Y. Rajendhra (Asian Journal of Chemistry, 2010)
Tea is an important dietary source of flavanols and flavonols. In vitro and animal studies provide strong evidence that tea polyphenols may possess the bioactivity to affect the pathogenesis of several chronic diseases, especially cardio vascular diseases and cancer. However, the results from epidemiological and clinical studies of the relationship between tea and health are mixed. Clinical trials employing putative intermediary indicators of disease, particularly biomarkers of oxidative stress status, suggest tea polyphenols could play a role in the pathogenesis of cancer and heart disease.